2017
DOI: 10.5194/tc-11-2117-2017
|View full text |Cite
|
Sign up to set email alerts
|

Wave–ice interactions in the neXtSIM sea-ice model

Abstract: Abstract. In this paper we describe a waves-in-ice model (WIM), which calculates ice breakage and the wave radiation stress (WRS). This WIM is then coupled to the new sea-ice model neXtSIM, which is based on the elasto-brittle (EB) rheology. We highlight some numerical issues involved in the coupling and investigate the impact of the WRS, and of modifying the EB rheology to lower the stiffness of the ice in the area where the ice has broken up (the marginal ice zone or MIZ). In experiments in the absence of wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…By calibrating C a and C w properly, free drift with no internal stress or wave effect, as might be caused by Stokes drift (Yiew et al, 2017), slope sliding (Grotmaack & Meylan, 2006), or wave radiation stresses (Masson, 1991), produces very good model results compared with observations, especially under storm conditions. Williams et al (2017) and Boutin et al (2019) recently integrated wave radiation stresses into large-scale numerical models that include wave attenuation and wave-induced ice breakup, based on the wave-ice interaction model of Williams et al (2013aWilliams et al ( , 2013b. They found that large wave radiation stresses, proportional to the wave attenuation rate, remain concentrated at the edge (Williams et al, 2017); wind and ocean stresses dominate ice drift over longer distances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By calibrating C a and C w properly, free drift with no internal stress or wave effect, as might be caused by Stokes drift (Yiew et al, 2017), slope sliding (Grotmaack & Meylan, 2006), or wave radiation stresses (Masson, 1991), produces very good model results compared with observations, especially under storm conditions. Williams et al (2017) and Boutin et al (2019) recently integrated wave radiation stresses into large-scale numerical models that include wave attenuation and wave-induced ice breakup, based on the wave-ice interaction model of Williams et al (2013aWilliams et al ( , 2013b. They found that large wave radiation stresses, proportional to the wave attenuation rate, remain concentrated at the edge (Williams et al, 2017); wind and ocean stresses dominate ice drift over longer distances.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (2017) and Boutin et al (2019) recently integrated wave radiation stresses into large-scale numerical models that include wave attenuation and wave-induced ice breakup, based on the wave-ice interaction model of Williams et al (2013aWilliams et al ( , 2013b. They found that large wave radiation stresses, proportional to the wave attenuation rate, remain concentrated at the edge (Williams et al, 2017); wind and ocean stresses dominate ice drift over longer distances. Moreover, Williams et al (2017) found that wave radiation stresses are appreciable only for wave periods < 10 s; the measurements reported here have dominant periods > 15 s. The small floes observed during our measurements, smaller floes than tested by Williams et al (2017), would induce even weaker radiation stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIZ is a complex and heterogeneous environment, which comprises of ice floes of arbitrary shape and a variety of ice types from newly formed ice to fragmented multi-year ice. While surface waves are expected to be a dominant process controlling the total extent of the MIZ as well as the size distribution of ice floes, there still exist large uncertainties about the exact mechanisms for wave attenuation in sea ice (Williams et al, 2013(Williams et al, , 2017Kohout et al, 2014;Meylan et al, 2014). In addition to affecting the floe size distribution, the attenuation of surface gravity waves is also important in controlling the extent of the MIZ via the wave radiation stress (Liu et al, 1993;Williams et al, 2017;Sutherland & Dumont, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Parameterizations of waveice interactions for large-scale continuum models (i.e., those in which ice is treated as a continuous mass rather than as discrete particles) are crucial for further development of those models. However, although appreciable effort has been made in that direction in recent years (Dumont et al, 2011;Doble and Bidlot, 2013;Squire et al, 2013;Williams et al, 2013Williams et al, , 2017; The WAVEWATCH III®Development Group , WW3-DG; Bennetts et al, 2017), our understanding of many aspects of wave-ice interactions is still too limited to allow formulating such parameterizations, especially those suitable for a wide range of conditions. Strong fragmentation of the in the above-mentioned parameterizations by Williams et al (2013), Bennetts et al (2017), and others.…”
Section: Introductionmentioning
confidence: 99%